Host ZAP activity correlates with the levels of CpG suppression in primate lentiviruses - Rayhane Nchioua; Dorota Kmiec; Veronika Krchlikova; Sarah Mattes; Sabrina Noettger; Frederic Bibollet-Ruche; Ronnie M. Russell; Konstantin M. J. Sparrer; Thomas Charpentier; Frédéric Tardy; Steven E. Bosinger; Daniel Sauter; et al. (Proceedings of the National Academy of Sciences, 2025)
Zinc-finger antiviral protein (ZAP) is thought to drive the suppression of CpG dinucleotides in many viruses to mimic the composition of their host genomes. However, in vivo evidence is sparse. Here, we investigated the reasons for unusually high CpG levels in SIVmus and SIVmon from mustached and mona monkeys, descendants of one of the precursors of HIV-1. We show that SIVmus is not resistant to ZAP inhibition. Instead, these Cercopithecus monkey hosts differ from other primate species by a splice site mutation and express the poorly active extralarge XL rather than the highly active L isoform of ZAP. Similarly, higher CpG levels in endogenous prosimian lentiviruses were associated with low activity of the corresponding host lemur ZAPs. In addition, lemur genes also show lower CpG suppression than other primates. Thus, the antiviral activity of ZAP not only affects suppression of CpG dinucleotides in viral transcripts but possibly also host genomes.